2021
DOI: 10.1038/s41467-021-21921-x
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 RNA editing enzyme regulates R-loop formation and genome stability at telomeres in cancer cells

Abstract: ADAR1 is involved in adenosine-to-inosine RNA editing. The cytoplasmic ADAR1p150 edits 3’UTR double-stranded RNAs and thereby suppresses induction of interferons. Loss of this ADAR1p150 function underlies the embryonic lethality of Adar1 null mice, pathogenesis of the severe autoimmune disease Aicardi-Goutières syndrome, and the resistance developed in cancers to immune checkpoint blockade. In contrast, the biological functions of the nuclear-localized ADAR1p110 remain largely unknown. Here, we report that ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…The deregulation of genes involved in immunity is likely elicited by the silencing of the p150 ADAR1 isoform. However, other biological processes related to the p110 isoform [56], also silenced in our study, were deregulated, such as DNA damage checkpoint (GO:0,000,077). It is highly probable that both ADAR1 isoforms contribute to the growth defect observed in vitro and in vivo after ADAR1 silencing [57]; however, our study design did not allow us to distinguish the specific isoform responsible for CDK13 editing and this should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 54%
“…The deregulation of genes involved in immunity is likely elicited by the silencing of the p150 ADAR1 isoform. However, other biological processes related to the p110 isoform [56], also silenced in our study, were deregulated, such as DNA damage checkpoint (GO:0,000,077). It is highly probable that both ADAR1 isoforms contribute to the growth defect observed in vitro and in vivo after ADAR1 silencing [57]; however, our study design did not allow us to distinguish the specific isoform responsible for CDK13 editing and this should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 54%
“…Although the majority of research efforts to understand mechanisms of R-loop regulation has focused on the helicase family of proteins for their ability to resolve these structures 12 , 13 , 22 , 30 , 33 , 69 , several reports also implicate proteins without known helicase activity in R-loop regulation 20 , 21 , 70 . Replication protein A (RPA), a single-strand DNA binding protein, is known to localize to R-loop structures in vivo where it stimulates the activity of RNase H to disrupt R-loops 20 .…”
Section: Discussionmentioning
confidence: 99%
“…5B ). Interestingly, it was previously shown that R-loops at telomeres can be edited by ADAR1 37 , leading to A→I edits 38 and a large body of evidence now supports the idea that these RNA editing enzymes tend to exhibit off-target effects. Because inosine pairs with cytosine, such off-target editing events on genomic R-loops could be reported as A→G errors by our circ-seq assay.…”
Section: Resultsmentioning
confidence: 91%